Understanding August Wilson - Bogumil, Mary L., 1955- (Understanding contemporary American literature., 1999)
"Understanding August Wilson provides readers with a comprehensive view of the thematic structure of Wilson's plays, the placement of his plays within the context of American drama, and the distinctively African American experiences and traditions that Wilson dramatizes."--BOOK JACKET. "In this critical study Mary L. Bogumil argues that Wilson gives voice to disfranchised and marginalized African Americans who have been promised a place and a stake in the American dream but find access to the rights and freedoms promised to all Americans difficult. The author maintains that Wilson not only portrays African Americans and the predicaments of American life but also sheds light on the atavistic connection African Americans have to their African ancestors. Bogumil explains that the playwright both perpetuates and subverts the tradition of American drama in order to expose the distinct differences between the white American and the African American experiences."--Jacket